Native tongue eaudiobook Skink series, book 2. - Hiaasen, Carl (Skink, 1992)
Ex-reporter Joe Winder had been working in the public relations department of a sleazy family entertainment park, The Amazing Kingdom of Thrills, when he chanced upon a news-breaking story inspired by the disappearance of two blue-tongued voles and the bizarre death of Orky, the killer whale.